Highly emissive pyrrolo[1,2-a]quinoxaline based narrow band fluorescent sensors for detection of nitroaromatics and their application in spot paper test - Aniket Karpe; Aniket Parab; Gokul Ganesan; Jatin Lade; Pravin Walke; Atul Chaskar (Chemical Physics Impact, 2024)
In the modern day, explosive detection is essential to public safety, and fluorescent small molecules have gained popularity for their quick and accurate detection. Herein, we present the design and synthesis of a series of pyrrolo[1,2-a]quinoxaline-based conjugated small organic fluorophores (PQ-Ph-OH, PQ-Ph-NMe, PQ-Ph-OMe, PQ-Ph-Me, and PQ-Ph-CN) as fluorescence-based sensors for explosive molecules. The sensor molecules were synthesized in good to excellent yields using a dehomologative functionalization strategy. They exhibited excellent photophysical characteristics, which was tunable based on the substituent on the phenyl linker at position 3. DFT studies showed that the pyrroloquinoxaline moiety could act as an on-demand electron donor or acceptor, depending on the phenyl substituent. The molecules also exhibited solid state emission due to twisted geometry around the CC single bond between the heterocyclic scaffold and the phenyl derivative. This resulted in low band intense emission for the synthesized molecules. In the presence of electron-deficient nitroaromatic explosives, all the fluorophores showed excellent fluorescence quenching. Detection limits in the range of 10−4 M were obtained for all the fluorophores. Stern-Volmer plots show high values of binding constants, indicating good interaction between the fluorophores and the explosive molecules. The mechanism of sensing was confirmed by UV-PL spectral overlap and fluorescence lifetime measurements, which suggest a static quenching based on the formation of a ground state complex. Owing to solid state emissions in some of the derivatives, the synthesized molecules were applied to paper strips for spot detection of explosive molecules.